Role of Information and Communication Technology (ICT) for Rural Development through E-Governance Initiatives - Bhuvana, M.; Vasantha, S. (International Journal of Psychosocial Rehabilitation, 2020)
Among the various Asian Countries, India is the country with nearly 70% of the people resides in rural areas. People living in remote villages faces various challenges in accessing various governmental services developed for the benefit of rural development. Information and Communication Technology (ICT) act as a gateway in providing various opportunities to reach the rural citizens and contributor for reducing the poverty. Productivity can be increased in rural areas by improving the usage of ICT (Information and Communication Technology). Through different e-governance services like Government to Government (G2G), Government to Citizens (G2C), Government to Businesses (G2B) and Government to Employees (G2E) our Indian Government has desire in transforming the government interaction with the citizens in an electronic form. This research paper is an attempt to examine the various e-governance services designed and developed by Government of India (GOI) to deliver their information and services in remote villages for rural development. This paper also analyses the role of Information and Communication Technology towards rural development through e-governance initiatives.